La prevención de la ideación suicida en adolescentes en el municipio de Ciudad Bolívar – Antioquia desde el año 2012 hasta el 2014 (2015)
Suicide is one of the 10 leading causes of death in the world, and one of the top three in people between 15 and 55 years old. About one million people kill themselves on a year and 20 million more try. Suicide is a multi-causal phenomenon which involves biological, cultural, family, economic, psychosocial factors, among others. As a strategy to prevent the phenomenon of suicide (attempt, and completed suicide ideation) the Health Secretary of the municipality of Ciudad Bolívar adopted the National Plan of Public Health whereby the prevention of suicidal behavior is sought, seeking to transform habits lives of the youth of the town, through the strategy of life skills proposed by the WHO, the strategy is to allow the participants to become agents of change in the environments in which they operate